The Determinant of Firm Value in Asean Market: Esg Initiatives as Intervening Variable - Safitri, Maria; Muharam, Harjum; Pangestuti, Irene Rini Demi (Journal of Posthumanism, 2025)
This study investigates the impact of leverage, cash flow, and firm size on firm value in the ASEAN market, with Environmental, Social, and Governance (ESG) initiatives acting as a mediating variable. Drawing on stakeholder and signaling theories, the study develops a conceptual framework that integrates both financial and non-financial factors in determining firm value. Using panel data from 50 non-financial companies listed on ASEAN stock exchanges between 2019 and 2023, the study employs Structural Equation Modeling using Partial Least Squares (SEM-PLS) to analyze both direct and indirect relationships. The results show that leverage, cash flow, and firm size all have significant and positive effects on firm value. Among these, firm size exerts the strongest direct influence. In addition to their direct effects, these variables also significantly affect ESG initiatives. ESG initiatives themselves have a significant positive impact on firm value, reinforcing their strategic importance in enhancing corporate reputation and stakeholder trust. Importantly, ESG initiatives are found to mediate the relationship between financial indicators and firm value, with firm size again showing the strongest indirect effect through ESG. These findings suggest that ESG practices not only complement financial performance but also enhance the value-creation process in firms operating within the ASEAN region. This study contributes to the growing body of literature on sustainable finance by providing empirical evidence of the mediating role of ESG initiatives in linking financial strategy to firm value. The results have practical implications for corporate managers and policymakers aiming to align financial and sustainability goals.